'I see what you mean': Using visual data collection methods to explore leadership curriculum planning. (January 2018) - Reid, Anna; Koglbauer, René
This article reports on the use of a visual methods approach to collecting and analysing data in relation to the area of leadership curriculum development. The focus of the study is the structure of the current leadership curriculum for the National Professional Qualifications (NPQs) in England. In particular, the authors explore the extent to which a visual method of data collection enhances their understanding of underlying structures of the NPQs, and the extent to which they can adopt findings from the study to influence the planning and preparation of future programmes. Participants in the study volunteered to attend an international conference workshop on leadership, management and administration. This was the forum for data collection. Purposive sampling ensured a prior knowledge of the theoretical framework underpinning our work and objectivity in that none of the participants were involved in the delivery of NPQ programmes in England. Findings suggest that the current NPQ programme structure lacks the flexibility required in order to provide a meaningful professional development experience. In relation to the theoretical underpinnings of this study, findings also highlight areas to be addressed when undertaking new NPQ programme development and delivery.